A dynamic emotional model for agent societies - Rincon, J. A. (2016)
This paper presents a first approximation of a dynamic emotional model to be employed in agent societies. The proposed model is based on the PAD emotional model and allows the representation of the emotional contagion phenomena of a heterogeneous group of agents which are capable of express emotions. Moreover, the proposal allows the definition of the social emotion of this group of agents. The model is mainly based on three elements: personality, empathy and affinity. These elements allow the characterization of each individual, causing them susceptible to vary in some degre the emotions of other individuals.